Performances of self-compacting concrete incorporating recycled fine aggregate - Rishabh Tyagi; Pradeep Kumar Goyal (Materials Research Express)
This research examines the performance of M40-grade Self-Compacting Concrete (SCC) with Recycled Fine Aggregate (RFA) as a partial substitute for Natural Fine Aggregate (NFA), emphasizing fresh, mechanical, and durability characteristics. Mixtures were formulated in accordance with IS 10262:2019 and EFNARC recommendations, using RFA as a substitute for NFA at 0%, 20%, and 40% replacement levels. Furthermore, 40% of the cement was replaced with Ground Granulated Blast Furnace Slag (GGBS), and a polycarboxylic ether (PCE) based superplasticizer, constituting 0.8% of the cement weight, was used to enhance flowability. The fresh qualities, such as slump flow, L-box ratio, V-funnel time, and segregation resistance, increased with higher RFA content, with the 40% RFA mix exhibiting superior flowability and passing ability. Mechanical strengths (compressive, flexural, and splitting tensile) improved with curing age in all mixtures. The 40% RFA mix attained a 28-day compressive strength of 59.8 MPa, surpassing the control mix at 54.8 MPa, and exhibited enhanced strength progression up to 90 days (66.0 MPa compared to 61.5 MPa for the control mix). Durability measures, including water absorption, porosity, and void ratio, decreased with increasing RFA concentration, although apparent density rose, indicating a denser and more impermeable matrix. This results from the synergistic effects of superior mix design, internal curing, and improved particle packing. This work distinctly examines the viability of integrating up to 40% RFA in structural-grade SCC, beyond the conventional upper threshold documented in previous studies. The use of GGBS and PCE-based admixtures offers a comprehensive strategy for attaining superior fresh, mechanical, and durability performance, hence fostering a sustainable and high-strength SCC solution.